Gaya Kepemimpinan Muslim Dalam Meningkatkan Etos Kerja Pendidik SDIT AL- Madinah Kebumen - Panuju, Rachmansyah; Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2022)
The correlation of leadership style and work ethic is interrelated, if the leadership style is implemented in accordance with the character of employees, the work ethic will improve. Therefore, work ethic becomes an important basic thing to support the success of an institution. The research objective was to determine the Muslim leadership style and to see the suitability between Muslim leadership styles and the work ethic of educators at SDIT Al-Madinah Kebumen. The research method used a descriptive qualitative approach by analyzing and concluding data from interviews obtained selectively through informants. This study provides the results that the leadership style is applied using a democratic type which can create a balance between work and mood so that there is harmony between Islamic leadership style and the work ethic of educators.